2014
DOI: 10.1007/s11295-014-0775-4
|View full text |Cite
|
Sign up to set email alerts
|

Extensive pollen flow in a natural fragmented population of Patagonian cypress Austrocedrus chilensis

Abstract: Habitat fragmentation might significantly affect mating and pollen dispersal patterns in plant populations, contributing to the decline of remnant populations. However, wind-pollinated species are able to disperse pollen at longer distances after opening of the canopy. Our objectives were to characterize the mating system parameters and to estimate the average distance of effective pollen dispersal in the windpollinated conifer Austrocedrus chilensis. We sampled 19 "mother trees," 200 progeny, and 81 additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
11
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 62 publications
(77 reference statements)
3
11
2
Order By: Relevance
“… 32 . The mean values for Ho and He obtained using SSR markers in this germplasm were higher than those reported for other Chinese firs 24 – 26 and other conifers 33 – 35 , but lower than those in Abies chensiensis and Austrocedrus chilensis 36 , 37 ; this suggests that the level of genetic diversity in this germplasm is moderate. Outcrossing and wind-pollination may explain the considerable level of polymorphisms in this species 38 – 41 .…”
Section: Discussioncontrasting
confidence: 72%
“… 32 . The mean values for Ho and He obtained using SSR markers in this germplasm were higher than those reported for other Chinese firs 24 – 26 and other conifers 33 – 35 , but lower than those in Abies chensiensis and Austrocedrus chilensis 36 , 37 ; this suggests that the level of genetic diversity in this germplasm is moderate. Outcrossing and wind-pollination may explain the considerable level of polymorphisms in this species 38 – 41 .…”
Section: Discussioncontrasting
confidence: 72%
“…H E (0.584) obtained using SSR markers was also higher for some conifers, including Pinus bungeana (H E : 0.249; Zhao et al, 2014), Pinus massoniana (H E : 0.536; Bai et al, 2014), and Pinus dabeshanensis (H E : 0.458; Xiang et al, 2015). However, it is lower than that of Abies chensiensis (H E : 0.803; Li et al, 2012), and Austrocedrus chilensis (H E : 0.865; Colabella et al, 2014). Further studies have indicated that the genetic diversity of this germplasm resource is moderate.…”
Section: Discussionmentioning
confidence: 98%
“…Limited gene flow typically leads to reduced genetic diversity, increased population structure, and inbreeding within populations (Byrne et al, 2008; Sherwin & Moritz, 2000; Young et al, 1996), which were not consistent with our findings. Other studies focused on forest trees in fragmented landscapes found that regardless of moderate‐to‐high habitat fragmentation, many insect‐pollinated tree species were able to maintain high levels of gene flow across isolated patches through increased long distance pollen dispersal (Bacles, Burczyk, Lowe, & Ennos, 2005; Colabella, Gallo, Moreno, & Marchelli, 2014; Nason & Hamrick, 1997; Wang, Stephen, & Xiao‐Yong, 2011). Our study findings are consistent with these studies as shown by the high level of gene flow present across fragmented C. canadensis populations.…”
Section: Discussionmentioning
confidence: 99%